Models for irrigation scheduling in a canal command area - Sudsaisin Kaewrueng; Murty, V.V.N.; Wiboon Boonyatharokul; Goto, Akira; The Starr Foundation (U .S .A . ) (Bangkok : Asian Institute of Technology, 1989)
In canal command areas water is supplied through a network of canals and related structures. Different projects follow different delivery patterns. Simulation models for scheduling irrigations were developed to study the irrigation schedules required in canal command areas. The crop selected were paddy (both transplanted and broadcasted) and sugarcane . The required data in terms of soil properties and climatic information was collected from the selected area. Irrigation schedules were developed both for sugarcane and paddy based upon allowable soil moisture depletions. The irrigation schedules predicted by the model were compared with t hose actually followed by the farmers. It was seen in dry season 1989 over irrigation as indicated by model simulation has resulted. This requires further verification in other seasons. The study gave the procedure for evaluating the service unit efficiency which is useful for understanding the water use in different outlets of a large irrigation projects.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1989
Keywords: Irrigation scheduling